Constitutional Identity and Relationship Between European Union Law and National Law of the Slovak Republic - Krunková, Alena (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This book chapter addresses identity, an elementary theoretical concept, which also has penetrated the field of constitutional law. The identity of the Constitution as a fundamental law is a variable that determines the direction of the state. It was created in parallel with the creation of the Constitution. However, the Constitution is not immutable; its dynamism reflects, as a minimum, social change. The first part addresses the concepts of constitutional identity versus national identity. The second part analyses the impact of selected constitutional amendments on the identity of the Constitution in the Slovak Republic and the constitutional aspects of the relationship between European Union Law and the National Law of the Slovak Republic.Keywords: identity, authority, constitution, European Union law, Slovak Republic, national law